2020
DOI: 10.17513/use.37320
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Material and Chemical Composition of Sedimentary Matter of Rainfall on the Territory of the Kaliningrad Region Rf

Abstract: 2 Федеральный исследовательский центр комплексного изучения Арктики им. академика Н.П. Лаверова РАН, Архангельск На окружающую среду Калининградской области большое влияние оказывает трансграничный атмосферный перенос антропогенных примесей, превышающий выбросы локальных источников эмиссий в 5-7 раз. Приведены результаты исследования количественного, вещественного и химического составов нерастворимых микрочастиц дождевых осадков. В рамках работы было собрано и обработано 29 проб дождевых осадков разных сезонов… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A good correlation was also observed between Na and V and Cr (r = 0.84 for both), Mg and V and Cr (r = 0.83 and 0.84, respectively), K-Ca (r = 0.74), Ca-Fe (r = 0.81), V-Sr (r = 0.80), Cr-Sr (r = 0.74), Mn-Ba (r = 0.71), Co-Ni (r = 0.71), Co-Zn (r = 0.91), Ni-Cu (r = 0.88), Ni-Zn (r = 0.88), Ni-Ba (r = 0.90), and Cu-Ba (r = 0.91). According to Topchaya [32], if the significant correlation relationship between the concentrations of elements r > 0.87, then the elements are of lithogenic origin; when r = 0.70-0.87, then the elements are of both lithogenic and anthropogenic origin. In [49], as the authors indicated the elements that have a good correlation relationship with Al (r > 0.5), we can assume the lithogenic origin of these elements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good correlation was also observed between Na and V and Cr (r = 0.84 for both), Mg and V and Cr (r = 0.83 and 0.84, respectively), K-Ca (r = 0.74), Ca-Fe (r = 0.81), V-Sr (r = 0.80), Cr-Sr (r = 0.74), Mn-Ba (r = 0.71), Co-Ni (r = 0.71), Co-Zn (r = 0.91), Ni-Cu (r = 0.88), Ni-Zn (r = 0.88), Ni-Ba (r = 0.90), and Cu-Ba (r = 0.91). According to Topchaya [32], if the significant correlation relationship between the concentrations of elements r > 0.87, then the elements are of lithogenic origin; when r = 0.70-0.87, then the elements are of both lithogenic and anthropogenic origin. In [49], as the authors indicated the elements that have a good correlation relationship with Al (r > 0.5), we can assume the lithogenic origin of these elements.…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements can be carried by the winds. The authors of [29,32] indicate that the main reason for bringing dust with trace element content is the wind that comes from industrial facilities. Apart from Na, Mg, K, Ca, Fe, Co, Ni, and Sr, the other studied elements had concentrations in rainwater collected in the open area that were lower than in rainwater under the forest canopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation